Donor-Specific Anti-Human Leukocyte Antigen Antibodies Predict Prolonged Isolated Thrombocytopenia and Inferior Outcomes of Haploidentical Hematopoietic Stem Cell Transplantation. (18th April 2017) - Zhao, Xiaosu; Zhao, Xiangyu; Huo, Mingrui; Fan, Qiaozhen; Pei, Xuying; Wang, Yu; Zhang, Xiaohui; Xu, Lanping; Huang, Xiaojun; Liu, Kaiyan; Chang, Yingjun
Abstract : Prolonged isolated thrombocytopenia (PT) after allogeneic stem cell transplantation (allo-SCT) has a great impact on transplant outcome. In this study, we performed a retrospective analysis to investigate the association of donor-specific anti-human leukocyte antigen (HLA) antibodies (DSAs) with PT in 394 patients who underwent unmanipulated haploidentical blood and marrow transplantation (HBMT). For HLA antibody positive samples with a median fluorescent intensity (MFI) > 500, DSAs were further examined. A total of 390 patients (99.0%) achieved sustained myeloid engraftment. Of the 394 cases tested, 45 (11.4%) were DSA positive. The cumulative incidence of PT in this cohort of patients was 9.9 ± 1.5%. The incidence of PT was higher in patients with a MFI ≥ 1000 compared with those with a MFI < 1000 (16.8 ± 6.4% versus 7.4 ± 1.4%, P = 0.05 ). Multivariate analysis showed that the presence of DSAs (MFI ≥ 1000) was correlated to PT (hazard ratio (HR) 3.262; 95% confidence interval (CI), 1.339–7.946; P = 0.009 ) and transplant-related mortality (HR 2.320; 95% CI, 1.169–4.426; P = 0.044 ). Our results, for the first time, suggest an association of DSAs with PT after unmanipulated HBMT. It would help screen out the suitable donor and guide intervention. This indicated that DSAs should be incorporated in the algorithm for unmanipulated HBMT.